Scrub typhus: a hidden causative agent for pyrexia of unknown origin cases in a tertiary care hospital from Jhalawar, Rajasthan - Nehra, Nikhil K.; Charan, Karan S.; Bilonia, Shailendra K. (International Journal of Research in Medical Sciences, 2022)
Background: Scrub typhus presents as an acute, febrile, exanthematous illness. Due to its non-specific and varied clinical presentation, this is underdiagnosed. Low index of suspicion among clinicians, and lack of diagnostic facilities also keeps it undiagnosed. This study was carried out to know the seroprevalence of scrub typhus in a tertiary care centre with pyrexia of unknown origin (PUO) and to compare a rapid test with IgM enzyme-linked immunosorbent assay (ELISA) for the diagnosis of scrub typhus. Methods: This cross-sectional analytical study was conducted for a period of 1 year. The study population comprised mainly 320 patients attending outdoor and indoor patients admitted to a tertiary care hospital with fever and related symptoms. The serum samples were tested for IgM ELISA, and rapid card test. Results: The mean age group of the study population was 35–60 years, of which 30 cases were positive. The major predisposing factors for scrub typhus infection were crops and animals around houses. The sensitivity and specificity of both, card test and IgM ELISA were 100%. Conclusions: In this study, 9.3% of febrile patients were positive for scrub typhus. Dengue, malaria and typhoid were the common coinfections found in scrub typhus, positive patients. Early identification of cases and treatment at the earliest will prevent complications.